Welcome to our community

Be a part of something great, join today!

Trigonometric challenge

  • Thread starter
  • Admin
  • #1

anemone

MHB POTW Director
Staff member
Feb 14, 2012
3,689
Express $\cos^7 x+\cos^7 \left( x+\dfrac{2 \pi}{3} \right)+\cos^7 \left( x+\dfrac{4 \pi}{3} \right)$ in terms of $\cos 3x$.
 

Opalg

MHB Oldtimer
Staff member
Feb 7, 2012
2,708
Express $\cos^7 x+\cos^7 \left( x+\dfrac{2 \pi}{3} \right)+\cos^7 \left( x+\dfrac{4 \pi}{3} \right)$ in terms of $\cos 3x$.
This is best done using complex numbers. Let $\lambda = e^{ix}$, $\omega = e^{2\pi i/3}$. Then $\cos x = \frac12(\lambda + \lambda^{-1})$, $\cos \left( x+\frac{2 \pi}{3} \right) = \frac12(\lambda\omega + \lambda^{-1}\omega^{-1})$, $\cos \left( x+\frac{4 \pi}{3} \right) = \frac12(\lambda\omega^2 + \lambda^{-1}\omega^{-2})$, and $$ \cos^7 x+\cos^7 \left( x+\tfrac{2 \pi}{3} \right)+\cos^7 \left( x+\tfrac{4 \pi}{3} \right) = 2^{-7}\bigl((\lambda + \lambda^{-1})^7 + (\lambda\omega + \lambda^{-1}\omega^{-1})^7 + (\lambda\omega^2 + \lambda^{-1}\omega^{-2})^7\bigr).$$ Now expand by the binomial theorem and use the facts that $\omega^3=1$ and $1+\omega+\omega^2=0$: $$\begin{aligned} \cos^7 x+\cos^7 \left( x+\tfrac{2 \pi}{3} \right)+\cos^7 \left( x+\tfrac{4 \pi}{3} \right) &= 2^{-7}\bigl(\lambda^7(1+\omega^7+\omega^{14}) + 7\lambda^5(1+\omega^5+\omega^{10}) + 21\lambda^3(1+\omega^3+\omega^6) + 28\lambda(1+\omega+\omega^2)\bigr. \\ & \qquad {} + \bigl.28\lambda^{-1}(1+\omega^{-1}+\omega^{-2}) + 21\lambda^{-3}(1+\omega^{-3}+\omega^{-6}) + 7\lambda^{-5}(1+\omega^{-5}+\omega^{-10}) + \lambda^{-7}(1+\omega^{-7}+\omega^{-14})\bigr) \\ &= 2^{-7}\bigl((\lambda^{7} + \lambda^{-7})(1+\omega+\omega^2) + 7(\lambda^{5} + \lambda^{-5})(1+\omega+\omega^2) \\ & \qquad {} + 21(\lambda^{3} + \lambda^{-3})(1+1+1) + 28(\lambda + \lambda^{-1})(1+\omega+\omega^2)\bigr) \\ &= 2^{-7}\cdot21\cdot3(\lambda^{3} + \lambda^{-3}) = \frac{63}{2^6}\cos(3x). \end{aligned}$$ Thus the answer is $(1-2^{-6})\cos(3x).$
 
  • Thread starter
  • Admin
  • #3

anemone

MHB POTW Director
Staff member
Feb 14, 2012
3,689
Thank you again Opalg for participating! I think we used the pretty same approach, because the coefficients of the terms that we have in our methods are all the same.

My solution:

According to the power reduction formula, we have

$\cos^7 x=\dfrac{35\cos x+21\cos 3x+7\cos5x+\cos7x}{64}$

hence

$\cos^7 \left(x+\dfrac{2 \pi}{3} \right)=\dfrac{35\cos \left(x+\dfrac{2 \pi}{3} \right)+21\cos 3\left(x+\dfrac{2 \pi}{3} \right)+7\cos5\left(x+\dfrac{2 \pi}{3} \right)+\cos7\left(x+\dfrac{2 \pi}{3} \right)}{64}$

$\cos^7 \left(x+\dfrac{4 \pi}{3} \right)=\dfrac{35\cos \left(x+\dfrac{4 \pi}{3} \right)+21\cos 3\left(x+\dfrac{4 \pi}{3} \right)+7\cos5\left(x+\dfrac{4 \pi}{3} \right)+\cos7\left(x+\dfrac{4 \pi}{3} \right)}{64}$

Notice that

$35\cos x+35\cos \left(x+\dfrac{2 \pi}{3} \right)+35\cos \left(x+\dfrac{4 \pi}{3} \right)=35\left( \cos x+\cos \left(x+\dfrac{2 \pi}{3} \right) \right)+35\cos \left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35\left( 2 \cos \left(\dfrac{ \pi}{3} \right) \cos \left( x+\dfrac{ \pi}{3} \right) \right)+35\cos \left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35 \cos \left( x+\dfrac{ \pi}{3} \right) +35\cos \left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35 \left( \cos \left( x+\dfrac{ \pi}{3} \right) +\cos \left(x+\dfrac{4 \pi}{3} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35 \left( 2\cos \left( \dfrac{ \pi}{2} \right) \cos \left(x+\dfrac{5 \pi}{6} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=0$

Similarly,

$21\cos 3x+21\cos 3\left(x+\dfrac{2 \pi}{3} \right)+21\cos 3\left(x+\dfrac{4 \pi}{3} \right)=21\cos 3x+21\cos (3x+2 \pi)+21\cos (3x+2 \pi)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=21\cos 3x+21\cos 3x+21\cos 3x$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=63\cos 3x$

$7\cos5x+7\cos5\left(x+\dfrac{2 \pi}{3} \right)+7\cos5\left(x+\dfrac{4 \pi}{3} \right)=7\left( \cos 5x+\cos 5\left(x+\dfrac{2 \pi}{3} \right) \right)+7\cos 5\left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7\left( 2 \cos \left(\dfrac{ 5\pi}{3} \right) \cos \left( 5x+\dfrac{ 5\pi}{3} \right) \right)+7\cos \left(5x+\dfrac{20 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7 \cos \left( 5x+\dfrac{ 5\pi}{3} \right) +7\cos \left(5x+\dfrac{20 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7 \left( \cos \left( 5x+\dfrac{ 5\pi}{3} \right) +\cos \left(5x+\dfrac{20 \pi}{3} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7 \left( 2\cos \left( \dfrac{ 5\pi}{2} \right) \cos \left(5x+\dfrac{25 \pi}{6} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=0$

and finally

$\cos7x+\cos7\left(x+\dfrac{2 \pi}{3} \right)+\cos7\left(x+\dfrac{4 \pi}{3} \right)=\left( \cos 7x+\cos 7\left(x+\dfrac{2 \pi}{3} \right) \right)+\cos 7\left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=\left( 2 \cos \left(\dfrac{ 7\pi}{3} \right) \cos \left( 7x+\dfrac{ 7\pi}{3} \right) \right)+\cos \left(7x+\dfrac{28 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;= \cos \left( 5x+\dfrac{ 5\pi}{3} \right) +7\cos \left(5x+\dfrac{20 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=\left( \cos \left( 7x+\dfrac{ 7\pi}{3} \right) +\cos \left(7x+\dfrac{28 \pi}{3} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=2 \left( 2\cos \left( \dfrac{ 21\pi}{2} \right) \cos \left(7x+\dfrac{35 \pi}{6} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=0$

Therefore

$\cos^7 x+\cos^7 \left( x+\dfrac{2 \pi}{3} \right)+\cos^7 \left( x+\dfrac{4 \pi}{3} \right)=0+\dfrac{63 \cos 3x}{64}+0+0=\dfrac{63 \cos 3x}{64}$
 

kaliprasad

Well-known member
Mar 31, 2013
1,309
Thank you again Opalg for participating! I think we used the pretty same approach, because the coefficients of the terms that we have in our methods are all the same.

My solution:

According to the power reduction formula, we have

$\cos^7 x=\dfrac{35\cos x+21\cos 3x+7\cos5x+\cos7x}{64}$

hence

$\cos^7 \left(x+\dfrac{2 \pi}{3} \right)=\dfrac{35\cos \left(x+\dfrac{2 \pi}{3} \right)+21\cos 3\left(x+\dfrac{2 \pi}{3} \right)+7\cos5\left(x+\dfrac{2 \pi}{3} \right)+\cos7\left(x+\dfrac{2 \pi}{3} \right)}{64}$

$\cos^7 \left(x+\dfrac{4 \pi}{3} \right)=\dfrac{35\cos \left(x+\dfrac{4 \pi}{3} \right)+21\cos 3\left(x+\dfrac{4 \pi}{3} \right)+7\cos5\left(x+\dfrac{4 \pi}{3} \right)+\cos7\left(x+\dfrac{4 \pi}{3} \right)}{64}$

Notice that

$35\cos x+35\cos \left(x+\dfrac{2 \pi}{3} \right)+35\cos \left(x+\dfrac{4 \pi}{3} \right)=35\left( \cos x+\cos \left(x+\dfrac{2 \pi}{3} \right) \right)+35\cos \left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35\left( 2 \cos \left(\dfrac{ \pi}{3} \right) \cos \left( x+\dfrac{ \pi}{3} \right) \right)+35\cos \left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35 \cos \left( x+\dfrac{ \pi}{3} \right) +35\cos \left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35 \left( \cos \left( x+\dfrac{ \pi}{3} \right) +\cos \left(x+\dfrac{4 \pi}{3} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=35 \left( 2\cos \left( \dfrac{ \pi}{2} \right) \cos \left(x+\dfrac{5 \pi}{6} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=0$

Similarly,

$21\cos 3x+21\cos 3\left(x+\dfrac{2 \pi}{3} \right)+21\cos 3\left(x+\dfrac{4 \pi}{3} \right)=21\cos 3x+21\cos (3x+2 \pi)+21\cos (3x+2 \pi)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=21\cos 3x+21\cos 3x+21\cos 3x$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=63\cos 3x$

$7\cos5x+7\cos5\left(x+\dfrac{2 \pi}{3} \right)+7\cos5\left(x+\dfrac{4 \pi}{3} \right)=7\left( \cos 5x+\cos 5\left(x+\dfrac{2 \pi}{3} \right) \right)+7\cos 5\left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7\left( 2 \cos \left(\dfrac{ 5\pi}{3} \right) \cos \left( 5x+\dfrac{ 5\pi}{3} \right) \right)+7\cos \left(5x+\dfrac{20 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7 \cos \left( 5x+\dfrac{ 5\pi}{3} \right) +7\cos \left(5x+\dfrac{20 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7 \left( \cos \left( 5x+\dfrac{ 5\pi}{3} \right) +\cos \left(5x+\dfrac{20 \pi}{3} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=7 \left( 2\cos \left( \dfrac{ 5\pi}{2} \right) \cos \left(5x+\dfrac{25 \pi}{6} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=0$

and finally

$\cos7x+\cos7\left(x+\dfrac{2 \pi}{3} \right)+\cos7\left(x+\dfrac{4 \pi}{3} \right)=\left( \cos 7x+\cos 7\left(x+\dfrac{2 \pi}{3} \right) \right)+\cos 7\left(x+\dfrac{4 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=\left( 2 \cos \left(\dfrac{ 7\pi}{3} \right) \cos \left( 7x+\dfrac{ 7\pi}{3} \right) \right)+\cos \left(7x+\dfrac{28 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;= \cos \left( 5x+\dfrac{ 5\pi}{3} \right) +7\cos \left(5x+\dfrac{20 \pi}{3} \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=\left( \cos \left( 7x+\dfrac{ 7\pi}{3} \right) +\cos \left(7x+\dfrac{28 \pi}{3} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=2 \left( 2\cos \left( \dfrac{ 21\pi}{2} \right) \cos \left(7x+\dfrac{35 \pi}{6} \right) \right)$

$\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;=0$

Therefore

$\cos^7 x+\cos^7 \left( x+\dfrac{2 \pi}{3} \right)+\cos^7 \left( x+\dfrac{4 \pi}{3} \right)=0+\dfrac{63 \cos 3x}{64}+0+0=\dfrac{63 \cos 3x}{64}$
1st step to decompose $cos ^7x$ as sum of cos x , cos 3x terms etc is good

using cos x + cos $( x+\dfrac{2 \pi}{3}$ ) + cos $( x+\dfrac{4 \pi}{3} $) = 0 for 5x and 7x can be made as zero

as cos 5 $( x+\dfrac{2 \pi}{3} $) = cos $( 5 x+\dfrac{4 \pi}{3} $) so on and all terms except 3x can be made zero. this reduces number of steps
 
Last edited:
  • Thread starter
  • Admin
  • #5

anemone

MHB POTW Director
Staff member
Feb 14, 2012
3,689
1st step to decompose $cos ^7x$ as sum of cos x , cos 3x terms etc is good

using cos x + cos $( x+\dfrac{2 \pi}{3}$ ) + cos $( x+\dfrac{4 \pi}{3} $) = 0 for 5x and 7x can be made as zero

as cos 5 $( x+\dfrac{2 \pi}{3} $) = cos $( 5 x+\dfrac{4 \pi}{3} $) so on and all terms except 3x can be made zero. this reduces number of steps
Duh...I should have thought of this earlier so that that would save me all the trouble struggling with the latex!(Angry)
 

mathbalarka

Well-known member
MHB Math Helper
Mar 22, 2013
573
anemone said:
I should have thought of this earlier so that that would save me all the trouble struggling with the latex!
One way of aligning the equation is to use
Code:
\begin{align}...\end{align}
to save your time.
 
  • Thread starter
  • Admin
  • #7

anemone

MHB POTW Director
Staff member
Feb 14, 2012
3,689
One way of aligning the equation is to use
Code:
\begin{align}...\end{align}
to save your time.
Thanks, Balarka! I appreciate you telling me this!